Laju Paparan Radiasi Sinar-X pada Dinding Laboratorium Diagnostik ATRO Bali - Dewi, Nunung Purwati; Trisnawati, Ni Luh Putu; Iffah, Maghfirotul (BULETIN FISIKA, 2021)
Research has been carried out on the rate of exposure to X-ray radiation on the walls of the ATRO Bali diagnostic laboratory. The dose of X-ray radiation exposure was measured using a surveymeter indoors and outdoors on the primary radiation retaining wall (A), secondary radiation retaining wall (B and D) and leakage radiation retaining wall (C) by setting the exposure factor at 80 kV tube voltage, 200 mA tube current and 0.160 seconds time. The results of the radiation exposure dose measurement on all walls are used to calculate the radiation exposure rate. The results of the calculation of the average rate of exposure to X-ray radiation on wall A is 1.106 × 10 -7 mR/h, wall B is 1.600 × 10 -7 mR/h, wall C is 6.217 × 10 -8 mR/h and wall D of 7.668 × 10 -8 mR/h. The results of the calculation of the rate of exposure to X-ray radiation on the walls outside the laboratory were obtained at 0 mR/hour. From these results it can be seen that the rate of exposure to X-ray radiation in the Bali ATRO diagnostic laboratory is still below the dose limit value (NBD) recommended by Bapeten Perka No. 8 of 2011 amounted to 0.57 mR/h for radiation workers and 0.03 mR/h for the community. Abstrak Telah dilakukan penelitian mengenai laju paparan radiasi sinar-X pada dinding laboratorium diagnostik ATRO Bali. Dosis paparan radiasi sinar-X diukur menggunakan surveymeter di dalam dan di luar ruangan pada dinding penahan radiasi primer (A), dinding penahan radiasi sekunder (B dan D) dan dinding penahan radiasi bocor (C) dengan mengatur faktor eksposi pada tegangan tabung 80 kV, arus tabung 200 mA dan waktu 0,160 detik. Hasil pengukuran dosis paparan radiasi pada suatu dinding digunakan untuk menghitung laju paparan radiasi rata-rata. Hasil perhitungan rata-rata laju paparan radiasi sinar-X pada dinding A sebesar 1,106 × 10 -7 mR/h, dinding B sebesar 1,600 × 10 -7 mR/h, dinding C sebesar 6,217 × 10 -8 mR/h dan dinding D sebesar 7,668 × 10 -8 mR/h. Hasil perhitungan laju paparan radiasi sinar-X pada dinding di luar laboratorium diperoleh sebesar 0 mR/h. Dari hasil tersebut terlihat bahwa laju paparan radiasi sinar-X di laboratorium diagnostik ATRO Bali masih di bawah nilai batas dosis (NBD) yang direkomendasikan oleh Perka Bapeten No. 8 tahun 2011 sebesar 0,57 mR/h untuk pekerja radiasi dan 0,03 mR/h untuk masyarakat.